2017
DOI: 10.11114/jets.v5i6.2405
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Service Learning and Volunteerism Activities on University Students in Turkey

Abstract: The general purpose of this study is to determine the awareness and acquisitions obtained with service activities by the students studying on undergraduate level in Eskişehir Anadolu University in 2016-2017 education year and involve in service learning and volunteerism activities. The study was designed according to qualitative research method and the case study was used. The data of the study was collected with semi-structured interview technique. Descriptive analysis method was used in analysing the data. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In our view, institutions with significant international student populations could benefit by fostering volunteer groups, by increasing awareness of the importance of diversity in campus organizations, and by adapting new social integration strategies. There is a perception that the U.S. has a special historical connection with volunteerism (Ogilvie, 2004), but our study depends on the view that the ethos of volunteerism is essentially international (e.g., Boru, 2017; Sarfson and Albini, 2017). We see volunteerism not as an essentially American activity, but as a cross-cultural activity that lends itself particularly well to campus internationalization.…”
Section: Discussionmentioning
confidence: 99%
“…In our view, institutions with significant international student populations could benefit by fostering volunteer groups, by increasing awareness of the importance of diversity in campus organizations, and by adapting new social integration strategies. There is a perception that the U.S. has a special historical connection with volunteerism (Ogilvie, 2004), but our study depends on the view that the ethos of volunteerism is essentially international (e.g., Boru, 2017; Sarfson and Albini, 2017). We see volunteerism not as an essentially American activity, but as a cross-cultural activity that lends itself particularly well to campus internationalization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various studies are investigating the effectiveness of implementing these pedagogies in teaching practice, often in the form of case studies (e.g. Ayers et al, 2020;Baden & Parkes, 2013;Boru, 2017;Heiskanen et al, 2016;Konrad et al, 2020Konrad et al, , 2021Mintz & Tal, 2013Molderez & Fonseca, 2018), but also in the form of more…”
Section: The Role Of Pedagogical Approaches and Methods For Teaching ...mentioning
confidence: 99%
“…With its popularity, a substantial body of research on service-learning in higher education has suggested evidence of its positive impact on students’ cognitive and affective development. Previous studies have demonstrated that service-learning enhances cognitive development, such as students’ academic performance (Fredericksen, 2000 ; Markus et al, 1993 ) as well as personal and social development such as social responsibility (Kolenko et al, 1996 ), self-efficacy (Tucker & McCarthy, 2001 ), belongings to school and community (Soria et al, 2019 ), career development (Boru, 2017 ) problem solving, and communication skill (Tucker et al, 1998 ; Weiler et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%